Characteristics and Outcomes of Eldery Trauma in Samsun: A Retrospective Study - Kuloğlu, Muhammet Mustafa; Aydın, Berna; Turla, Ahmet; Levent, Fulya Zeynep (The Bulletin of Legal Medicine, 2023)
Objective: Traumas belonging to the population aged 65 and over continue to be a prominent health problem in the 21st century. In this study, we aimed to understand and illuminate the geriatric trauma cases admitted to the regional hospital in Samsun. Methods: The files and records on the hospital automation system of the cases aged 65 and over who came to the Emergency Department of Ondokuz Mayıs University Faculty of Medicine between 01.01.2011 and 31.12.2020 as a result of a traumatic event were retrospectively examined. The cases in our study were evaluated in terms of demographic characteristics, events that occurred, injured body area, hospitalization and length of stay, existing comorbidities, mortality. Results: Of the total 1960 cases, 65.8% of the cases were male and 34.2% were female. At the date of the event, 62.8% of the cases were in the 65-74 age range. The most common (36.1%) type of event was falling. It is found that the most (36.7%) frequently injured body area is the head and neck region, and the least (5.9%) is the pelvis. 68.7% of the cases were hospitalized and 135 cases died. Conclusion: The elderly population, which has begun to take a greater role in both social and business life; increased risk with trauma. Advancing age and existing comorbidities lead to a more serious outcome of trauma in the elderly compared to the young. Physicians should be cautious about performing a detailed examination, especially in terms of inadequacy in the records and suspicion of abuse/negligence.